The Effect of Temperature Variation and Storage Time of Plasma Citrate Samples on Protombin Time Values - Abdi Pertiwi, Dwi Liana; Diah Prihatiningsih; I Gusti Putu Agus Ferry Sutrisna Putra (CV. CENDIKIA JENIUS INDONESIA, 2025)
Prothrombin time (PT) testing is essential to evaluate blood clotting disorders; however, its results are strongly influenced by pre-analytical factors such as temperature and the storage duration of citrate plasma. This study aimed to determine the effect of temperature variations and storage time of citrate plasma on PT values. This experimental study with a cross-sectional approach used 20 citrate plasma samples obtained through accidental sampling. PT examinations were carried out at the Hematology Laboratory of the Denpasar Health Polytechnic in May 2024 using the CoaDATA 4004 instrument. Samples were tested immediately after centrifugation, then after storage at room temperature (20–25°C) and in a refrigerator (2–8°C) for 2 hours and 4 hours, respectively. Data were analyzed using normality tests, homogeneity tests, Repeated Measures ANOVA, and One-Way ANOVA. The results showed significant differences in PT values after 2- and 4-hour storage at both room and refrigerated temperatures (p=0.000). The average PT value immediately after collection was 12.2 seconds, increasing to 12.5 and 12.7 seconds at room temperature and to 12.9 and 13.1 seconds under refrigeration. Based on statistical tests, both storage temperature and duration affected citrate plasma PT values. Conclusion : PT testing should be performed as soon as possible after sample collection or with a delay of less than 2 hours at room temperature. If a longer delay is unavoidable, citrate plasma is recommended to be stored in a freezer (-20°C) with routine temperature monitoring to maintain coagulation factor stability.